2007
DOI: 10.1080/13813450701475201
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of the prevalence of the metabolic syndrome and its components in type 2 diabetic patients in two Caribbean islands using the new International Diabetes Federation definition

Abstract: There were high prevalence rates of the components of the MetS in both the islands of Tobago and Trinidad. Quantitatively, the aggregation of the components is higher in patients in Trinidad, which constitute greater risk for adverse cardiovascular outcome. Controlling central obesity should be the target in preventing MetS in the two islands.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
19
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 49 publications
0
19
0
Order By: Relevance
“…Thus, because of the peculiar limited economic resources available in the developing countries, diabetes co-morbidity and mortality rates are higher and more devastating in poor countries (Roglic & Unwin, 2009). Even with the limited research output from the developing countries, reports of high prevalence rates of cardiovascular risk factors in patients with type 2 diabetes are abundant in the medical literature (Ezenwaka et al, 2007(Ezenwaka et al, , 2009. Similarly, research on social and economic impact of diabetes have shown that the economic impact of diabetes and diabetes-related mortality rates are greater in poorer countries in the developing regions of the world (Roglic & Unwin, 2009;Tharkar et al 2010).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, because of the peculiar limited economic resources available in the developing countries, diabetes co-morbidity and mortality rates are higher and more devastating in poor countries (Roglic & Unwin, 2009). Even with the limited research output from the developing countries, reports of high prevalence rates of cardiovascular risk factors in patients with type 2 diabetes are abundant in the medical literature (Ezenwaka et al, 2007(Ezenwaka et al, , 2009. Similarly, research on social and economic impact of diabetes have shown that the economic impact of diabetes and diabetes-related mortality rates are greater in poorer countries in the developing regions of the world (Roglic & Unwin, 2009;Tharkar et al 2010).…”
mentioning
confidence: 99%
“…These reports suggest that there is the urgent need for more intense diabetes education tailored for prevention of diabetes complications. Poor glycaemic control and obesity are the central risk factors for cardiovascular disease in type 2 diabetes patients in the developing countries (Ezenwaka et al, 2007(Ezenwaka et al, , 2009). Previous nonpharmacological intervention studies in the developing countries targeting exercise, dietary modification or increased blood glucose monitoring have shown both relative risk reduction in the incidence of type 2 diabetes (Li et al, 2008;Ramachandran et al, 2006) and improved CHD risk profile in the patients studied (Ezenwaka et al, 2011;Sun et al, 2008).…”
mentioning
confidence: 99%
“…Patients were considered as type 2 diabetic if they had been managed on oral hypoglycaemic medication and/or diet/exercise since diagnosis (except on occasions when patients took insulin to control hyperglycaemia). The protocol was as previously published (Ezenwaka et al, 2007), briefly, the patients received information leaflets and posters explaining the objectives and protocol of the research study. Furthermore, a member of the research group addressed the patients during the clinics to explain the rationale for the study and subsequently the Research Assistant or Clinic Nurse took names and other information of patients who volunteered to participate in the study.…”
Section: Type 2 Diabetic Patientsmentioning
confidence: 99%
“…Obesity, especially abdominal obesity is now recognised as central to the metabolic syndrome (IDF, 2006;Alberti et al, 2006), and both generalised and abdominal obesity are prevalent in Tobago Island (Ezenwaka et al, 2007). It has been shown that the more overweight or obese a person is, the greater the degree of insulin resistance irrespective of the index of measurement (Farin et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have documented that diabetes can be prevented or complication can be decreased through education, increased physical activity and healthy food choices (Waxman, 2005). Globally, prevention strategies are being implemented to help educate and promote diabetes management, particularly for children in schools (Babwah et al, 2006;Ezenwaka et al, 2007). In Trinidad and Tobago, similar initiatives are ongoing to halt the rise in diabetes prevalence.…”
Section: Introductionmentioning
confidence: 99%